Questioning the Readiness of Manado as a Tourism Destination: Poor Service of Waitresses in the Local Restaurants - Towoliu, Benny Irwan; Sangari, Fonny; Permana, Dimas Ero (Journal of Indonesian Tourism and Development Studies, 2017)
In the last two decades, Manado local government has forwarded a Manado vision as a tourism destination. Due to this policy, many accommodations and restaurants are built here. Certainly, this is an opportunity for local people to work in the hospitality industry. Meanwhile, so far the tourism development industry is only physical, it was not supported by the human resource local tourism development, in this case, the waitresses who work in local restaurants. The research aims to examine the quality of service of waitresses who work in local restaurants. The research was conducted from October to December 2015, and locations of the area where data were taken are Mega Mas and Sabua Bulu Malalayang. These areas are the centers of local culinary industry. The research method used is descriptive qualitative supported by quantitative data. Field research includes a survey involving 116 respondents, observation and documentation, and the analysis by serv-qual method. Service quality measured based on visitors' perceptions of the five dimensional aspects. They are the tangible aspect, responsiveness aspect, assurance aspect and empathy aspect. Result of this research shows that service quality of local waitresses are still low, where service performance appraisal is 3.11 while the guest expectations of service quality were 4.47. Guest rating on the performance expectations of service and quality of service shows a minus value. This indicates that the guest is not satisfactory with the performance of services provided by a waitress with an average value of -1.35 satisfactions which means that the value of service of local waitress is ≤ 0. Recommendation is that the local governments should encourage business manager of local restaurants training to improve service quality of waitress. The methods of training suggested are video presentation, vestibule, role plays and case studies. Keywords: local restaurants, poor service, readiness of Manado, tourism destination, waitresses.